Restoration of oligodendrocyte pools in a mouse model of chronic cerebral hypoperfusion. - Jamie McQueen; Michell M Reimer; Philip R Holland; Yasmina Manso; Mark McLaughlin; Jill H Fowler; Karen Horsburgh (PLoS ONE, 2014)
Chronic cerebral hypoperfusion, a sustained modest reduction in cerebral blood flow, is associated with damage to myelinated axons and cognitive decline with ageing. Oligodendrocytes (the myelin producing cells) and their precursor cells (OPCs) may be vulnerable to the effects of hypoperfusion and in some forms of injury OPCs have the potential to respond and repair damage by increased proliferation and differentiation. Using a mouse model of cerebral hypoperfusion we have characterised the acute and long term responses of oligodendrocytes and OPCs to hypoperfusion in the corpus callosum. Following 3 days of hypoperfusion, numbers of OPCs and mature oligodendrocytes were significantly decreased compared to controls. However following 1 month of hypoperfusion, the OPC pool was restored and increased numbers of oligodendrocytes were observed. Assessment of proliferation using PCNA showed no significant differences between groups at either time point but showed reduced numbers of proliferating oligodendroglia at 3 days consistent with the loss of OPCs. Cumulative BrdU labelling experiments revealed higher numbers of proliferating cells in hypoperfused animals compared to controls and showed a proportion of these newly generated cells had differentiated into oligodendrocytes in a subset of animals. Expression of GPR17, a receptor important for the regulation of OPC differentiation following injury, was decreased following short term hypoperfusion. Despite changes to oligodendrocyte numbers there were no changes to the myelin sheath as revealed by ultrastructural assessment and fluoromyelin however axon-glial integrity was disrupted after both 3 days and 1 month hypoperfusion. Taken together, our results demonstrate the initial vulnerability of oligodendroglial pools to modest reductions in blood flow and highlight the regenerative capacity of these cells.